1993
DOI: 10.1128/mcb.13.12.7925
|View full text |Cite
|
Sign up to set email alerts
|

Premature termination of tubulin gene transcription in Xenopus oocytes is due to promoter-dependent disruption of elongation.

Abstract: We have shown previously that the Xenopus a-tubulin gene, XcxT14, exhibits premature termination of transcription when injected into oocyte nuclei. The 3' ends of prematurely terminated transcripts are formed immediately downstream of a stem-loop sequence found in the first 41 bp of the 5' leader. We show here, using deleted constructs, that premature termination requires the presence only of sequences from -200 to +19 relative to the initiation site. Deletion of the stem-loop does not increase the production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1994
1994
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…The promoter of the a-tubulin gene XaT14 is extremely active in the oocyte injection assay [18] and possesses consensus binding sites for many different transcriptional activators, including a heat shock element and a reverse CCAAT box (though not a Y-box). Linker scanner mutations that replace any one or two of the binding sites result in only minor reductions in promoter activity [14], consistent with the complex promoter likely for a gene that is specifically expressed in a large number of different cell types [ 181. Experimental identification of the promoter elements normally required for ovarian expression of XaT14 may therefore be difficult because of the large variety of transcription factors stored in oocytes for later use in developing embryos.…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…The promoter of the a-tubulin gene XaT14 is extremely active in the oocyte injection assay [18] and possesses consensus binding sites for many different transcriptional activators, including a heat shock element and a reverse CCAAT box (though not a Y-box). Linker scanner mutations that replace any one or two of the binding sites result in only minor reductions in promoter activity [14], consistent with the complex promoter likely for a gene that is specifically expressed in a large number of different cell types [ 181. Experimental identification of the promoter elements normally required for ovarian expression of XaT14 may therefore be difficult because of the large variety of transcription factors stored in oocytes for later use in developing embryos.…”
Section: Introductionmentioning
confidence: 70%
“…Morgan, unpublished observations). Previous work with XaT14 [14,18,191 has suggested that the extreme efficiency of its complex promoter in injected oocytes is a fortuitous consequence of its containing many potential binding sites for transcriptional activators that presumably enable promoter activity in diverse cell types. The store of varied transcription factors stockpiled in the oocyte for embryonic development could thus impart unusually high activity to XaT14 promoters upon injection.…”
Section: Xat207 Promoter Organisationmentioning
confidence: 99%
See 1 more Smart Citation
“…Along similar lines, Meulia et al have reported that mutations altering the c-myc P2 TATA box had two effects: a decrease in overall transcription and a decrease in transcription termination (41). In the Xenopus cx-tubulin gene, mutations which disrupted the TATA box also led to a decrease in transcription and a decrease in the number of prematurely terminated transcripts (17). One hypothesis put forward by both groups centers on the fact that overall levels of transcription in these mutants were substantially reduced.…”
Section: Discussionmentioning
confidence: 86%
“…Less is known regarding regulation of tubulin gene expression in vertebrates. TATA boxes are generally present in vertebrate ␣-and ␤-tubulin promoters (29,30), and high level expression of a Xenopus ␣-tubulin gene, X␣T14, in oocytes is regulated by three CCAAT boxes, a "heat-shock-like" element (all located 60 -200 bp upstream of the transcription start site), and their corresponding transcription factors (31). Cotranslational regulation of tubulin mRNA stability also contributes to control of cellular tubulin levels (32).…”
mentioning
confidence: 99%